Effects of Heat Stress at Different Grain‐Filling Phases on the Grain Yield and Quality of Waxy Maize. Issue 2 (14th March 2014) - Lu, Dalei; Sun, Xuli; Yan, Fabao; Wang, Xin; Xu, Renchao; Lu, Weiping
ABSTRACT: Effects of heat stress (mean day/night temperatures of 35.2/16.1 and 27.4/15.6°C for heat stress and control, respectively) during different grain‐filling phases (1–10, 11–20, 21–30, 31–40, and 1–40 days after pollination [DAP]) on the grain yield and quality of waxy maize were investigated using two varieties. Heat stress decreased the number and weight of grains, thereby reducing grain yield. The effects of heat stress at an early grain development stage (before 20 DAP) were severe. Compared with the control, starch deposition was not affected by heat stress in Suyunuo5, and it was only decreased by heat stress at 1–10 DAP in Yunuo7. Protein content responses to heat stress were variety and stage dependent. Heat stress increased the iodine‐binding capacities of both varieties. Peak and breakdown viscosities were decreased by heat stress, and the effects gradually decreased with postponement of high temperature. Heat stress increased gelatinization temperature and retrogradation percentage for both varieties, and the response was stage dependent. Heat stress during the whole grain‐filling period increased the pasting and gelatinization temperatures but decreased gelatinization enthalpy. Changes in protein and starch contents as well as the proportion of long chains in amylopectin affected the pasting and thermal properties.